2. (2x-3)² = 1

3. 6x² - 24x = 0

4) 4m²+13m = 0

5. (2c + 1) (3c - 2) = 55

Topic: Solving quadratic equations by factoring

Log in to add a comment

2. (2x-3)² = 1

3. 6x² - 24x = 0

4) 4m²+13m = 0

5. (2c + 1) (3c - 2) = 55

Topic: Solving quadratic equations by factoring

Log in to add a comment

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

Number 2 lng alam ko eh.. the answer is 1.

hope it helps

-ninah :)

hope it helps

-ninah :)

The Brainliest Answer!

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

1) 2(a+6)² - 9 = 63

2(a+6)² = 72

(a+6)² = 36

a²+12a +36 -36= 0

a²+12a = 0

a(a+12) = 0

**a=0 ; a=-12**

2) (2x-3)² = 1

4x² -12x +9 =1

4x² -12x +9 -1 = 0

4x² -12x +8 = 0

4(x² -3x +2) = 0

x² -3x +2 = 0

(x-2) (x-1) = 0

**x=2 ; x=1**

3) 6x² - 24x = 0

6x(x-4) = 0

**x=0 ; x=4**

4) 4m²+13m = 0

m(4m +13) = 0

**m=0 ; m=-13/4**

5) (2c + 1) (3c - 2) = 55

6c² -c -2 = 55

6c² -c -2 -55 = 0

6c² -c -57 = 0

(6c -19) (c+3) = 0

**c=19/6 ; c=-3**

2(a+6)² = 72

(a+6)² = 36

a²+12a +36 -36= 0

a²+12a = 0

a(a+12) = 0

2) (2x-3)² = 1

4x² -12x +9 =1

4x² -12x +9 -1 = 0

4x² -12x +8 = 0

4(x² -3x +2) = 0

x² -3x +2 = 0

(x-2) (x-1) = 0

3) 6x² - 24x = 0

6x(x-4) = 0

4) 4m²+13m = 0

m(4m +13) = 0

5) (2c + 1) (3c - 2) = 55

6c² -c -2 = 55

6c² -c -2 -55 = 0

6c² -c -57 = 0

(6c -19) (c+3) = 0